Box-rent receipt, July 1888 (1888)
A box-rent receipt for Ah Louis (spelled 'Luis' in the document). This rental lasted for a quarter of 1888, from July 14 to September 30. The price was 75 cents. On the back of the receipt are regulations for the rental. Chinese script is written over the regulations.